A SOUTH INDIAN CASE OF KOHLSCHUTTER-TONZ SYNDROME(KTS) WITH SPEECH ABNORMALITY - Dr. Billa Vikas; Dr. Sravyasri Mukthavaram; Sunil Kumar Kasuvojvala; Venu Ettaveni (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Kohlscutter-Tonz syndrome (KTS) is a rare autosomal recessive genetic disorder first described in 1974, characterized by seizures, intellectual disability, and abnormalities of teeth and other organs. It is caused by pathogenic variants in the ROGDI gene, with only 44 confirmed cases reported to date. Objective: Investigate the genetic cause and natural history of an affected South Indian patient from a consanguineous family to inform the diagnosis and management of KTS. Methods: Targeted gene sequencing of clinically relevant genes was performed using custom capture and Illumina sequencing. Sequencing reads were aligned to GRCh38, and variants called with GATK, then annotated using VariMAT, ClinVar, OMIM, and HGMD. Anti-seizure medications, therapies, and multidisciplinary management strategies used for 44 patients with Kohlscutter-Tonz syndrome were reviewed as a basis for tailored treatment. Results: Targeted sequencing identified a novel homozygous ROGDI frameshift variant (p. Thr202AsnfsTer26) in the proband. Analysis of 44 published KTS patients found anti-seizure medications-controlled seizures in 10-50% of cases. The prognosis is usually poor due to refractory epilepsy, developmental regression, and early mortality. Conclusion: This case adds to knowledge of the molecular basis and phenotype of KTS. Symptomatic treatment with anti-seizure medications provides limited efficacy, reflecting a lack of disease-modifying options. Further research on the ROGDI pathway may enable the development of targeted therapies to improve long-term outcomes.